„Alle sind auseinander gerissen worden. Keines weiß, wo das andere ist.“ - Thomas Huonker (Österreichische Zeitschrift für Geschichtswissenschaften, 2014)
Analyzing the documents produced by the catholic organisation Seraphisches Liebeswerk Solothurn (SLS) about a female yenish ward from the region of Solothurn placed in different non-yenish families and institutions in different Swiss regions, the article shows the views and ideologies oft the educational personal of the SLS in the years between 1930 and 1950. An important aim of this education with the help of institutions like resident schools, children work in farming families, workhouses and jails was to isolate the ward and to separate it from the family of origin. Results of this educational approach were identity problems, rebellion, threats with suicide, episodes of running away and loosing religion. An important part of this kind of education was a strongly religious element; essential, too, was the cooperation and broad consent with public institutions and with other private institutions involved in the persecution of the Yenish in Switzerland like the foundation Pro Juventute.